Machining of Nitride Ceramics Using Elastic Tool with Discrete Cutting Profile - L.V. Sudnik; D.F. Ustinovich; V.I. Pribylsky (Механика машин, механизмов и материалов, 2009)
The paper discusses distinctive features of machining of constructional nitride ceramics using fiber composites with various abrasive modifiers. The regressive models obtained reflect the dependence of metal removal on cutting speed and type of abrasive modifier when changing the values of the main technological parameters. It is established that machining productivity is increased by a factor of 1,9 to 3,2 with simultaneous surface roughness decrease.